Proceedings of the 15th ACM Asia Conference on Computer and Communications Security 2020
DOI: 10.1145/3320269.3384725
|View full text |Cite
|
Sign up to set email alerts
|

Post-Quantum TLS on Embedded Systems: Integrating and Evaluating Kyber and SPHINCS+ with mbed TLS

Abstract: We present our integration of post-quantum cryptography (PQC), more specifically of the post-quantum KEM scheme Kyber for key establishment and the post-quantum signature scheme SPHINCS + , into the embedded TLS library mbed TLS. We measure the performance of these post-quantum primitives on four different embedded platforms with three different ARM processors and an Xtensa LX6 processor. Furthermore, we compare the performance of our experimental PQC cipher suite to a classical TLS variant using elliptic curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Moreover, with respect to the time 𝑧, Mosca estimated since 2015 [8] that there is a 1/7 chance of breaking RSA-2048 by 2026 and a 1/2 chance by 2031. Therefore, incorporating post-quantum ciphers in the TLS protocol is currently a significant research field (see, e.g., [9][10][11][12][13][14] ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, with respect to the time 𝑧, Mosca estimated since 2015 [8] that there is a 1/7 chance of breaking RSA-2048 by 2026 and a 1/2 chance by 2031. Therefore, incorporating post-quantum ciphers in the TLS protocol is currently a significant research field (see, e.g., [9][10][11][12][13][14] ).…”
Section: Introductionmentioning
confidence: 99%
“…In [22], Bürstinghaus-Steinbach et al showed the integration of the post-quantum key encapsulation mechanism (KEM) scheme Kyber for key establishment and the post-quantum signature scheme SPHINCS+ into the embedded TLS library mbedTLS [1]. They measured the performance of these post-quantum primitives on four different embedded platforms and presented the challenges regarding large certificates chain and slow signing process during the TLS handshake protocol.…”
Section: Related Workmentioning
confidence: 99%
“…They concluded that these challenges affect the use of embedded systems as TLS server but do not necessarily prevent them from acting as TLS client. While the writers of [22] recommended that the use of hardware accelerators may be considered to speed up the SPHINCS+ computations [22], no countermeasures were suggested for the huge size of the chain of trust.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations